Glucose- and pH-Responsive Nanogated Ensemble Based on Polymeric Network Capped Mesoporous Silica - Tan, Lei; Yang, Mei-Yan; Wu, Hai-Xia; Tang, Zhao-Wen; Xiao, Jian-Yun; Liu, Chuan-Jun; Zhuo, Ren-Xi (ACS applied materials & interfaces, 2015)
In this paper, a glucose and pH-responsive release system based on polymeric network capped mesoporous silica nanoparticles (MSN) has been presented. The poly(acrylic acid) (PAA) brush on MSN was obtained through the surface-initiated atom transfer radical polymerization (SI-ATRP) of t-butyl acrylate and the subsequent hydrolysis of the ester bond. Then the PAA was glycosylated with glucosamine to obtain P(AA-AGA). To block the pore of silica, the P(AA-AGA) chains were cross-linked through the formation of boronate esters between 4,4-(ethylenedicarbamoyl)phenylboronic acid (EPBA) and the hydroxyl groups of P(AA-AGA). The boronate esters disassociated in the presence of glucose or in acidic conditions, which lead to opening of the mesoporous channels and the release of loaded guest molecules. The rate of release could be tuned by varying the pH or the concentration of glucose in the environment. The combination of two stimuli exhibited an obvious enhanced release capacity in mild acidic conditions (pH 6.0).